Orientacja seksualna jako prawo człowieka - Sobczak, Jacek (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
It should be noted that although legal standards to protect one’s sexual orientation are being developed, the instances of infringement on the rights of sexual minorities continue to occur. On the other hand, the loud, and frequently obscene, demonstrations of some representatives of these minorities, although organized for a good cause, obviously irritate traditional communities of many cities and towns. It seems that it would be much easier for the representatives of such minorities to be accepted if they tended to emphasize economic issues, the way it is done in the European Union. Their claims referring to this sphere seem to be able to win relatively easy support and understanding. In Poland it seems necessary to start a long-term, substantive discussion provided that the outlook on life is left alone and the economic issues are focused upon instead. However, one can assume that a hasty introduction of EU solutions will not necessarily be socially approved.